2022
DOI: 10.3390/nu14040900
|View full text |Cite
|
Sign up to set email alerts
|

A College Fast-Food Environment and Student Food and Beverage Choices: Developing an Integrated Database to Examine Food and Beverage Purchasing Choices among College Students

Abstract: Universities typically offer residential students a variety of fast-food dining options as part of the student meal plan. When residential students make fast-food purchases on campus there is a digital record of the transaction which can be used to study food purchasing behavior. This study examines the association between student demographic, economic, and behavioral factors and the healthfulness of student fast-food purchases. The 3781 fast-food items sold at the University of North Carolina at Charlotte fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…It is, therefore, not surprising that students’ food choices both on and near campus are also generally unhealthy. Most surveys have found that student purchases of food on campus (excluding dining halls) and near campus were associated with unhealthy foods, such as SSBs and fast foods high in fat and added sugars [ 41 , 42 , 43 ]. A survey of 209 first-year PHEI students found that 64% considered their eating habits off campus healthy, compared with only 56% on campus [ 44 ].…”
Section: How Do Campus Food Environments Affect Student Food Choice F...mentioning
confidence: 99%
“…It is, therefore, not surprising that students’ food choices both on and near campus are also generally unhealthy. Most surveys have found that student purchases of food on campus (excluding dining halls) and near campus were associated with unhealthy foods, such as SSBs and fast foods high in fat and added sugars [ 41 , 42 , 43 ]. A survey of 209 first-year PHEI students found that 64% considered their eating habits off campus healthy, compared with only 56% on campus [ 44 ].…”
Section: How Do Campus Food Environments Affect Student Food Choice F...mentioning
confidence: 99%
“…Previous research suggests college students have low intakes of fruits and vegetables [ 13 ], high intakes of fats [ 13 , 14 ], and high intakes of added sugars [ 14 ]. Most universities offer meal plans and food retailers on campus to provide students the convenience of staying on-site for meals; however, there is often limited support for healthy eating [ 15 , 16 , 17 , 18 ]. College students are more likely to be influenced by unhealthy food environments due to limited time for grocery shopping, inadequate cooking skills, and budget constraints [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Young adults, such as university students, purchase fast food at increasing levels due to low prices and time and budget constraints. Also, they complain about the unavailability of tasty, healthy, and affordable foods on-campus (Racine et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, even if fast-food restaurants offer healthier options, will consumers choose them over other alternatives? It is unclear whether providing consumers with healthy food options will result in their choice (Racine et al, 2022). Thus, marketing managers of fast-food restaurants may be hesitant to invest in healthy alternatives.…”
Section: Introductionmentioning
confidence: 99%